Studies of Electrical and Thermal Conductivities of Sheared Multi-Walled Carbon Nanotube with Isotactic Polypropylene Polymer Composites - Parvathalu Kalakonda; Yanial Cabrera; Robert Judith; Georgi Y. Georgiev; Peggy Cebe; Germano S. Iannacchione (Nanomaterials and Nanotechnology)
Polymer nanocomposite materials of higher thermal and electrical transport properties are important to nanotech‐ nology applications such as thermal management, packag‐ ing, labelling and the textile industry. In this work, thermal and electrical conductivities in nanocomposites of multi- walled carbon nanotubes (MWCNT) and isotactic polypro‐ pylene (iPP) are investigated in terms of MWCNT loading, temperature dependence, and anisotropy caused by melt shearing. IPP/MWCNT nanocomposites show a significant increase in thermal and electrical conductivity with increasing MWCNT loading, reaching 17.5 W/m K and 10-6 S/m, respectively, at a MWCNT 5.0 weight percentage at 40°C. The increase in MWCNT/iPP is more than would be expected based on the additivity rule, and suggests a reduction of the interfacial thermal electrical resistance at nanotube-nanotube junctions and the nanotube-matrix interface. The anisotropy in both conductivities was observed to be larger at low temperature and to disappear at higher temperature due to isotropic electrical and thermal contact in both directions. Oriented MWCNT/iPP nanocomposites exhibit higher electrical and thermal conductivities, attributed primarily by orientation of nanotubes due to the shearing fabrication process.